Implementation of E-Voting System for Student Union Government Elections - Aderibigbe I. Adekitan; Victor O. Matthews; Temitope M. John; Stanley Uzairue (Universitas Ahmad Dahlan, 2018)
Several records of violence during student body elections in higher institutions of learning can be found dating back to the 1988 Abu crisis. The causal factors are multifaceted, involving both internal factors within the institution and external factors, and interest parties like main stream politicians. Suspicion of the possibility of rigging during a planned election can trigger pre-election violence, while alleged rigging during the election or the vote counting process is the major cause of election unrest during student government elections. The voting process is typically manual, and it is done through the use of ballot boxes and papers. This is error prone, inefficient and susceptible to rigging. Preventing mistrust-induced election violence requires the deployment of a trustworthy alternative to the paper ballot system. In this study, an electronic voting system is developed using Visual Basic and Microsoft Access Database. The application performs voter authentication by verifying a pre-issued pin which is unique for each voter. The system is accurate and engages the participation and login of agents who are representatives of the candidates’ contesting for various offices thereby building trust in the process.